“Ein schlagartiger Einbruch der Ewigkeit in die Zeit” — On the Spatiality of Musical Time - Dideriksen, Lauge (Schweizer Jahrbuch für Musikwissenschaft, 2026)
Throughout history and across cultures, music and time have shared a special bond. Philosophers in the Western tradition have illustrated their theories of time with examples of music, while composers have written music that attempts to alter or even undermine our everyday experience of time. In an echo of medieval Christianity, twentieth century Buddhist philosophy, and 2000s rave culture, theorists such as Christopher Hasty describe the results of these efforts as a “spatialisation of time”. In this article, I go a step further and attempt to articulate a notion of musical time that is necessarily spatial. I argue that the modes in which time is contained in music—rhythm, microrhythm, and form—spatialise our experience of the time in which the music is itself contained. Thus investigating these “metaphors we hear by” facilitates a nuanced understanding of time in music and music in time.